Predictors of successful trial off continuous positive airway pressure and high flow nasal cannula in preterm infants <30 weeks' gestation: A retrospective study. Issue 4 (25th January 2022) - Mohsen, Nada; Nasef, Nehad; Elkhouli, Mohamed; Ghanem, Mohab; Dalby, Allison; Yoon, Eugene Woojin; Finan, Emer; Shah, Prakesh S; Mohamed, Adel
Abstract: Objectives: To identify the predictors of successful first trial off nasal continuous positive airway pressure (nCPAP). Methods: A retrospective cohort study of infants ≤29 weeks' gestation who required nCPAP for >24 h was conducted. Logistic regression was used to detect predictors for successful trial off nCPAP. Statistical analysis was performed using the SAS software. Results: A total of 727 infants were included in the analysis. Infants who were successful in their first trial off nCPAP ( n = 313) were of higher gestational age (GA) and birth weight (BW), as well as a higher proportion of female infants, compared with those who were not successful ( p < 0.01). When stratified by GA, a negative correlation was noted between GA and postmenstrual age at successful trial off nCPAP or high flow nasal cannula (HFNC) ( r = 0.45, p < 0.01). Logistic regression analysis showed that GA (odds ratio [OR] 1.13, 95% confidence interval [CI] [1.03–1.24], p = 0.01) and percentage of time spent with an oxygen saturation over 89% in the 24 h preceding the trial off nCPAP (OR 1.08, 95% CI [1.05–1.11], p = 0.00) were independent predictors for successful trial off nCPAP. Conclusion: Successful trial off nCPAP or HFNC in preterm infants is significantly associated with higher GA, BW, female gender, and the specific oxygen saturation histogram in the preceding 24‐h period.